Multiple mini-interviews as a selection tool for initial teacher education admissions - Metsäpelto Riitta-Leena; Utriainen Jukka; Poikkeus Anna-Maija; Muotka Joona; Tolvanen Asko; Warinowski Anu (Elsevier Ltd, 2022)
This study investigates the reliability of multiple mini interviews (MMIs) to select students for classroom and special education teacher programs (n = 418) using intraclass correlations and cross-classified multilevel modeling. The results indicated mostly small effects of clustering of applicants to different interviewers and five-station circuits. The largest variance components in the MMI total score were for applicants (63.3%) and measurement error (20.6%), while the variance component for the interviewer was relatively small (11.6–14.4%). The applicants' and interviewers' perceptions were positive. This study provides evidence for the use of MMIs as a reliable tool for initial teacher education selection.